Compound defects and thermoelectric properties in ternary CuAgSe-based materials1. Issue 26 (14th July 2015) - Wang, Xiaobei; Qiu, Pengfei; Zhang, Tiansong; Ren, Dudi; Wu, Lihua; Shi, Xun; Yang, Jihui; Chen, Lidong
<x xml:space="preserve">Abstract</x> Carrier concentrations dominated the TE properties in CuAgSe-based materials, which is a promising thermoelectric material near room temperature.